Inovasi Aplikasi Sikepo dalam Meningkatkan Kinerja Pegawai di Kabupaten Bojonegoro - Erlinda, Dilla Febri; Septian, Esa; Rupiarsieh (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In the application of the digital attendance system, problems still often occur, an online attendance system that can be misused by the absence of employees at the workplace. The purpose of this research is to find out the discipline of the State Civil Apparatus by innovating new developments about the location-based ASN attendance monitoring system called SiKepo, making it easier for employees to access this system from anywhere. Researchers used qualitative research techniques in this study, using a qualitative approach to the case study method. Based on the results of the study, the innovation of the SiKepo application can improve employee discipline, efficiency, and effectiveness. Because there is data monitoring where employees are required to leave in the morning, with attendance using electronics. And can also use a fingerprint machine that is connected to the application if there are system error problems. After the implementation of SiKepo, there was an increase in the percentage of attendance, which used to be employees who deliberately skipped school with an average of 5 to 6 times a month, now employees are more disciplined. However, frequent error constraints require the uprage system to be better.